2020
DOI: 10.11604/pamj.supp.2020.35.2.24950
|View full text |Cite
|
Sign up to set email alerts
|

Three COVID-19 cases with a long-term viral shedding period in Tunisia

Abstract: Novel coronavirus disease (COVID-19) caused by severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) has become a public health emergency of international concern. This was first emerged in Wuhan, Hubei Province, China, and then has become widespread all over the world. We report 3 cases (2 imported cases and 1 local case) with documented viral shedding (based on reverse transcription-polymerase chain reaction (RT-PCR) testing) of SARS-CoV-2 for 55, 59 and 63 days. Viral shedding duration was defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Altogether, these findings are consistent with the presence of a persisting nucleocapsid antigen reservoir resulting in enhanced N-specific Tfh cell activation in CN patients. Clinical reports have identified cases of persistent SARS-CoV-2 infection in the nasopharynx lasting up to 63 days (Bennasrallah et al, 2020) and many patients re-tested RT-PCR+ for SARS-CoV-2 up to 38 days post-discharge (Dao et al, 2021). Though many of our CN patients have not re-tested RT-PCR+ by nasal swab (data not shown), others have yet to be tested.…”
Section: Discussionmentioning
confidence: 90%
“…Altogether, these findings are consistent with the presence of a persisting nucleocapsid antigen reservoir resulting in enhanced N-specific Tfh cell activation in CN patients. Clinical reports have identified cases of persistent SARS-CoV-2 infection in the nasopharynx lasting up to 63 days (Bennasrallah et al, 2020) and many patients re-tested RT-PCR+ for SARS-CoV-2 up to 38 days post-discharge (Dao et al, 2021). Though many of our CN patients have not re-tested RT-PCR+ by nasal swab (data not shown), others have yet to be tested.…”
Section: Discussionmentioning
confidence: 90%
“…PCR testing can remain positive for several months after SARS-Cov-2 infection. [ 23 ] Although no patients were observed to have worsening respiratory symptoms or chest CT findings, persistent ongoing infection could not be fully ruled out. Regarding vasculopathy, serum D-dimer levels were mildly elevated in 3 patients, and normal in 3 patients.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed 14 articles separately ( Bennasrallah et al, 2020 ;Chen et al, 2020a ;Hase et al, 2020 ;Luvira et al, 2020 ;Lv et al, 2020 ;Shao et al, 2020 ;Xia et al, 2020 ;Xing et al, 2020 ;Xu et al, 2020 ;Tajima et al, 2020 ;Sakanashi et al, 2021 ;Uda et al, 2021 ;Wan et al, 2021 ;Zheng et al, 2021 ) that reported two or more RT-PCR tests on upper or lower respiratory tract specimens after symptom onset. Figure 3 shows positivity over time, with data regarding how many tests were performed and how many of these were positive in each period.…”
Section: Temporal Profile Of Rt-pcr Testsmentioning
confidence: 99%